A genome-phenome association study in native microbiomes identifies a mechanism for cytosine modification in DNA and RNA - Yang, Weiwei; Lin, Yu-Cheng; Johnson, William; Dai, Nan; Vaisvila, Romualdas; Weigele, Peter; Lee, Yan-Jiun; Corrêa, Ivan R, Jr; Schildkraut, Ira; Ettwiller, Laurence (eLife, 2021)
Shotgun metagenomic sequencing is a powerful approach to study microbiomes in an unbiased manner and of increasing relevance for identifying novel enzymatic functions. However, the potential of metagenomics to relate from microbiome composition to function has thus far been underutilized. Here, we introduce the Metagenomics Genome-Phenome Association (MetaGPA) study framework, which allows linking genetic information in metagenomes with a dedicated functional phenotype. We applied MetaGPA to identify enzymes associated with cytosine modifications in environmental samples. From the 2365 genes that met our significance criteria, we confirm known pathways for cytosine modifications and proposed novel cytosine-modifying mechanisms. Specifically, we characterized and identified a novel nucleic acid-modifying enzyme, 5-hydroxymethylcytosine carbamoyltransferase, that catalyzes the formation of a previously unknown cytosine modification, 5-carbamoyloxymethylcytosine, in DNA and RNA. Our work introduces MetaGPA as a novel and versatile tool for advancing functional metagenomics.
Keywords: functional metagenomics; DNA modification; RNA modification; 5-hydroxymethylcytosine carbamoyltransferase; GWAS; microbiome; MetaGPA